Software Requirement Readiness Levels (SrRL) - Rathachai Chawuthai (My University, 2024)
This paper introduces software requirement readiness levels (SrRL), which is a definition to determine the readiness level of each software requirement of a software system. Our proposed SrRL provides the definitions of 9 levels that are applied from the concept of technology readiness level (TRL), together with scenarios and recommendations to achieve each level. The contribution of this work expects that the SrRL can be a guideline for software development teams and criteria for accepting software systems.
Keywords: Software Engineering Techniques and Practices; Technology Assessment and Management; Software Engineering Research